O-Buoy6 Deployment - William Simpson (Arctic Data Center, 2016)
This data set contains O-Buoy Deployment data. Daily, hourly or continuous measurements over Arctic Ocean sea ice of ozone (O3), carbon dioxide (CO2), bromine (BrO), wind speed and direction, air temperature and relative humidity (RH), barometric pressure, latitude and longitude, Universal Coordinated Time (UTC), horizon pictures, heading, pitch and roll *** SEE INSTRUMENT README FILES IN DATASET ***These are final data. Note: due to instrument malfunction, ozone data are limited. *** Data Citation: Matrai PA, F Chavez, D Perovich, P Shepson, and WR Simpson (2012, Last Updated 2014-07-10): O-Buoy6 Deployment. UCAR/NCAR - CISL - ACADIS. Dataset. http://dx.doi.org/10.5065/D6V98626.